Effect of Anticoagulant Administration in patients Hospitalized with COVID-19; A study from Lahore, Pakistan - Marium Mazhar, Maaz Suhail Rana, Huda Sarwar, Rabbia Saleem, S. Irtaza Fatima, Roheen Sajjad, Hamad N. Rana, Hussein Chreif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The recognition of the relationship between thromboembolism in COVID-19 and poor clinical outcomes led to the use of anticoagulants in patients diagnosed with Covid-19. Aim: To determine the effects of anticoagulants in COVID-19 patients and to compare the effect of oral, subcutaneous, and combined anticoagulants on patient outcomes. Study design: Retrospective cohort study Place and duration: A private tertiary care hospital, in Lahore, from 1st April 2020 to 30 Sep 2020 Methodology: Data were collected from electronic and paper records of admitted patients with a confirmed diagnosis of COVID-19 on PCR or with a radiological diagnosis of COVID-19. A total of 179 patients were included in the study, 172 were given anticoagulation, out of these, 74 were given oral anticoagulation, 73 were given subcutaneous and 24 were given combination of oral and subcutaneous anticoagulants. Results: Among 172 patients on anticoagulants, 41(23.8%) expired while 131(76.2%) recovered. Among 7(100%) patients on no anticoagulation, 1(14.3%) patient expired while 6(85.7%) recovered. 19(11%) patients on anticoagulation progressed towards the need for invasive ventilation while 152(89%) patients did not need invasive ventilation. Among patients on subcutaneous anticoagulants, 27(37%) expired while 46(63%) recovered. 8(33.3%) patients on combined anticoagulants expired while 16(66.7%) recovered. 6(8.1%) patients on oral anticoagulants expired while 68(91.9%) recovered. Conclusion: Anticoagulation improves the outcome of COVID-19 patients and oral anticoagulation is better than subcutaneous and combined anticoagulation. Keywords: COVID-19, anticoagulant, Rivaroxaban, Enoxaparin